2009
DOI: 10.1097/phm.0b013e3181b71afe
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Life Satisfaction in Persons with Spinal Cord Injury During Inpatient Rehabilitation

Abstract: Life satisfaction already improves during inpatient rehabilitation. Functional status, pain, and secondary impairments must be treated adequately in multidisciplinary rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 38 publications
6
49
2
Order By: Relevance
“…One consistent finding from the studies included for review is that regardless of chronologic age, individuals with relatively new SCI (that is, p5 YPI) have the potential to improve their overall QoL and/ or various QoL domains. 22,[24][25][26][27][30][31][32][33][34] Age of SCI onset therefore does not appear to preclude high QoL, however, within the various age categories there are likely differing age-related factors that may potentially influence QoL. For example, in studies with samples with mean ages p29 years, individuals were found to have greater improvements in life satisfaction and QoL if they were students, lived independently, had a lower level injury, had overcome past medical problems and if they had accessible vans for transportation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One consistent finding from the studies included for review is that regardless of chronologic age, individuals with relatively new SCI (that is, p5 YPI) have the potential to improve their overall QoL and/ or various QoL domains. 22,[24][25][26][27][30][31][32][33][34] Age of SCI onset therefore does not appear to preclude high QoL, however, within the various age categories there are likely differing age-related factors that may potentially influence QoL. For example, in studies with samples with mean ages p29 years, individuals were found to have greater improvements in life satisfaction and QoL if they were students, lived independently, had a lower level injury, had overcome past medical problems and if they had accessible vans for transportation.…”
Section: Discussionmentioning
confidence: 99%
“…22,25 Further, life satisfaction as measured by the SWLS was shown to consistently improve at 5 YPI intervals over 30 years, 32 and another study using the same measure showed life satisfaction to generally improve with YPI and to improve to a greater degree for those women who were separated/divorced than for men. 26 Finally, among individuals in their 40s, van Koppenhagen et al 33 observed QoL, as assessed by a two-item study-specific measure, to improve during rehabilitation, and to remain stable from discharge to 1 year post discharge. In a follow-up study, van Leeuwen et al 34 observed five different QoL trajectories over 5 years, with most having either consistently low or intermediate QoL trajectories, followed by individuals with either consistently high or improving trajectories.…”
Section: Swlsmentioning
confidence: 99%
“…Mean QoL ratings of most subjects improved between 6 months and 1 year after SCI and remained relatively stable after the first year. 9 Similarly, a Dutch prospective cohort study 49 showed that life satisfaction improved during inpatient rehabilitation, especially during the first 3 months of active rehabilitation (which started at a mean time of 2 months after injury), remained stable during the first year after discharge. It thus appears that life satisfaction improves from an initial low level early after SCI, but only to a level substantially below that of the general population.…”
Section: Methodsmentioning
confidence: 99%
“…Yet most of the research to date on the effects of SCI-related pain on QoL have examined pain generally, without distinguishing between type. 10,[12][13][14][15][16][17][18][19]21 The few studies that distinguish between pain types have done so on somewhat of a de facto basis, for example, examining shoulder pain in manual wheelchair users 45,46 and therefore studying what was likely an above-level, nociceptive pain. In those studies, significant relationships were found between QoL and degree of nociceptive pain.…”
Section: Discussionmentioning
confidence: 99%
“…Within the first year following injury, persons with SCI-related pain were more likely to experience deterioration in satisfaction with life, 18 and less pain during the acute phases of injury was associated with a recovery of life satisfaction at 1 year follow-up. 19 Between the first and second year following SCI, increased pain interference was associated with a decrease in life satisfaction. 20 In one of the most extensive studies to date on the matter, only pain severity and functional limitations were significant predictors of persistently low life satisfaction from rehabilitation to 5 years post SCI.…”
Section: Introductionmentioning
confidence: 99%